2018
DOI: 10.1002/pc.24923
|View full text |Cite
|
Sign up to set email alerts
|

Poly(amino acid)/carbon nanotube nanocomposites with enhanced thermal, electrical, and mechanical properties

Abstract: Poly(amino acid) (PAA)‐based nanocomposites were synthesized by in situ melting polycondensation with various carbon nanotube (CNT) loadings; the morphology, thermal, mechanical, electrical, and biocompatible properties of the resulting nanocomposites were investigated and characterized. The nanotubes were dispersed within the polymer matrix without the need for coupling agents or surfactants. The crystallization temperature showed a gradual rise with increasing CNT loading, confirming that the nanotubes act a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Mahfuz et al [32] also observed about 5 °C increase in T g due to addition of CNTs to nylon filaments. This increase in T g might be due to restrictions in mobility of PAN chains, possibly as a result of formation of a strong interface between PAN and CNTs or crystallization of structure in the vicinity of CNTs [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Mahfuz et al [32] also observed about 5 °C increase in T g due to addition of CNTs to nylon filaments. This increase in T g might be due to restrictions in mobility of PAN chains, possibly as a result of formation of a strong interface between PAN and CNTs or crystallization of structure in the vicinity of CNTs [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to HA, other fillers with special morphologies and size were greatly reported, including carbon nanotubes, graphene oxide, carbon fiber and glass fiber and so on. [14,[31][32][33][34][35] These fillers all showed great improvement for composites, especially for the mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…22 The hydroxyproline and aminocaproic acid was blended and copolymerized by in situ melting polycondensation in the interest of improving the mechanical properties. 23 Therefore, methionine was employed into aminocaproic acid-based copolymers for improving the hydrophilicity and then increasing degradation ratio of PAA in this paper.…”
Section: Introductionmentioning
confidence: 99%